LTF Regulates the Immune Microenvironment of Prostate Cancer Through JAK/STAT3 Pathway - Zhao, Qi; Cheng, Yingying; Xiong, Ying (Frontiers in Oncology, 2021)
Background: The study of the immune microenvironment in prostate cancer (PRAD) has brought new opportunities for the current traditional treatment regimens. Therefore, our goal is to develop a universal immunodiagnostic marker to improve patient survival. Methods: Bioinformatics analysis: we collected 591 samples from the TCGA and GEO cohort and evaluated the abundance and distribution of immune cell members in the PRAD expression profile matrix in the mixed cell population by CIBERSORT, ESTIMATE, ssGSEA, and other methods. The target genes related to PRAD immune microenvironment and tumor mutation load were obtained by overlap analysis and verified by pan-cancer analysis. Cell experiment: the cell transfection scheme was designed, and the experiment was divided into three groups: overexpressing LTF group, empty plasmid group, and control group. After obtaining cells in each group, the gene and protein expression levels of LTF and signal transduction of STAT3 and GM-CSF in the above three groups were detected by Real-Time PCR and Western blot respectively. Finally, the level of GM-CSF secretion in the three groups was detected by ELISA. Results: Macrophages, resting mast cells, and plasma cells play an important role in PRAD immune microenvironment. In addition, high tumor mutation load (TMB) was positively correlated with lymph node metastasis in patients with prostate cancer. As the core gene of the PRAD immune microenvironment, the low expression of LTF in PRAD promotes the occurrence of immunodeficiency, prostate cancer, and the enrichment of the JAK/STAT3 signal pathway. Through cell experiment, it was found that the content of LTF mRNA and protein increased significantly, while the content of STAT3 and GM-CSF mRNA and protein decreased significantly in the over-expressed LTF group. The level of GM-CSF in the supernatant of cell culture was significantly decreased in the overexpression group of LTF. Conclusion: The core gene we proposed is one of the most promising biomarkers to improve the overall survival rate of PRAD, and provides an important theoretical basis for the study of the mechanism of the LTF-mediated JAK/STAT3 pathway in PRAD.